Girls gone wild : sex education through fanfiction in the Singapore state - Widodo, Felicia (2018)
The relationship between the Singapore state and Singaporeans has been understood by the scholars as materialist in nature, where the state promotes and defaults to the notion of "Asian values" in their goal of creating economically efficient citizens. These values work to censure displays of sex and sexuality. As a result, Singaporean adolescents turn to globalised mediums to explore their sexualities. This paper therefore seeks to understand the consumption of online fanfiction as a "third space" to negotiate notions of sex and sexual identities in contrast to the Asian sex education promulgated by the state and reinforced by society at large. In particular, focus is placed on the experiences of female young adults as the notion of Asian values is enforced on them two-fold: firstly as an economically productive citizen, and secondly as the biological site of procreation.